RARE-42. INCIDENCE AND BEHAVIOR OF CENTRAL NERVOUS SYSTEM INVOLVEMENT IN PATIENTS WITH HODGKIN'S LYMPHOMA. (11th November 2019) - Eduardo Silva Correia, Carlos; Malani, Rachna; DeAngelis, Lisa; Moskowitz, Alison
Abstract: INTRODUCTION: Central nervous system (CNS) involvement from Hodgkin's Lymphoma (HL) is rare, with a reported incidence of 0.07–0.5%. There is a paucity of data regarding its natural history and management. METHODS: In this retrospective single-institution review, we analyzed all adult patients with HL for CNS involvement (parenchymal or meningeal), who were evaluated at Memorial Sloan Kettering Cancer Center from January 2008 until December 2018. RESULTS: A total of 3478 patients with HL were identified, and CNS involvement was found in 10 patients (0.3%). All patients were symptomatic from CNS disease. Four patients had a synchronous presentation. The other 6 patients had a median time from systemic diagnosis to CNS involvement of 8 years (2.5–14). Two patients had radiographic evidence of leptomeningeal disease, however 4 had positive cerebrospinal fluid (CSF) cytology. At time of CNS involvement, 2 patients had confirmed transformation to Non-Hodgkin-Lymphoma on biopsy. 2 patients had EBV-positive HL. One patient died before treatment. Five patients received high-dose methotrexate (HD-MTX) for CNS disease. Of these patients, 1 died during treatment, 2 had partial responses, and 2 had complete response of both systemic and CNS disease; to date they are in remission. Three patients had varied responses to immunotherapy and cytotoxic chemotherapy. Removal of an immunosuppressive agent resolved disease in one EBV-positive patient. Median overall survival (OS) from diagnosis of HL was 10.6 years (1.1–21.2), and OS from time to CNS involvement was 6 years (0.2–15). CONCLUSION: The median time from diagnosis to CNS involvement, and OS from time of CNS involvement are higher than previously reported, which may be related to newer therapies for systemic disease. Neuroimaging should be used in conjunction with CSF for diagnostic accuracy. HD-MTX can be used to treat CNS and refractory systemic disease, as historically used for the latter.